2017
DOI: 10.1038/s41541-017-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of a novel simian adenovirus vaccine against lethal MERS-CoV challenge in a transgenic human DPP4 mouse model

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) is a novel zoonotic virus that causes severe respiratory disease in humans with a case fatality rate close to 40%, but for which no vaccines are available. Here, we evaluated the utility of ChAdOx1, a promising replication-deficient simian adenovirus vaccine vector platform with an established safety profile in humans and dromedary camels, for MERS-CoV vaccine development. Using a transgenic lethal BALB/c MERS-CoV mouse model we showed that single dose in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 16 publications
2
95
0
2
Order By: Relevance
“…Apart from the inactive whole virus particle [30], live attenuated virus with gene deletion [31] , four more vaccines which mainly contain S protein were studied. These include a virus-like particle which incorporated S protein into hepatitis virus or influenza virus protein [32,33]; virus vectors, such as modified vaccinia virus Ankara (MVA) or Adenovirus carrying S protein [34,35]; S protein subunit vaccine, like RBD-based protein [29,36]; and DNA vaccine which encodes the full length or part of the S protein gene [37,38]. Most of them have been tested in mouse models and showed the ability to elicit neutralizing antibodies.…”
Section: Research and Development Of Vaccinesmentioning
confidence: 99%
“…Apart from the inactive whole virus particle [30], live attenuated virus with gene deletion [31] , four more vaccines which mainly contain S protein were studied. These include a virus-like particle which incorporated S protein into hepatitis virus or influenza virus protein [32,33]; virus vectors, such as modified vaccinia virus Ankara (MVA) or Adenovirus carrying S protein [34,35]; S protein subunit vaccine, like RBD-based protein [29,36]; and DNA vaccine which encodes the full length or part of the S protein gene [37,38]. Most of them have been tested in mouse models and showed the ability to elicit neutralizing antibodies.…”
Section: Research and Development Of Vaccinesmentioning
confidence: 99%
“…In this study, potentially protective humoral and cellular immune responses were elicited in mice by immunization using a recombinant adenoviral-based vaccine encoding the S1 subunit of the MERS-CoV spike gene. Several studies have been published that constructed similar vaccines against MERS-CoV and tested their ability to induce production of neutralizing antibodies and other immune system components [13,14,17,[19][20][21][22][23]. The results of these studies were encouraging and showed that -12], and IL-4) in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several attempts to develop a protective vaccine against MERS-CoV [12][13][14][15][16][17][18][19][20][21][22][23]. Researchers around the world are focused on the spike protein as the main target for vaccine development against MERS-CoV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of the ChAdOx1 platform to a diverse range of emerging pathogens is supported by multiple studies demonstrating that a single dose of ChAdOx1-vectored vaccine fully protected inbred BALB/c mice, sheep, goats, and cattle from lethal Rift Valley fever, protected 100% of transgenic human dipeptidyl peptidase-4 mice from lethal Middle East respiratory syndrome, and offered inbred BALB/c mice sterilising protection from Zika virus infection [107][108][109][110]. Each of these vaccine candidates has potently induced antigen-specific T-cell responses and high titre neutralising antibodies [107][108][109][110][111].…”
Section: Replication-deficient Chimpanzee Adenovirus Vector Platformmentioning
confidence: 99%